The Case for Translanguaging in Black Immigrant Literacies. (November 2020) - Smith, Patriann
Black immigrant youth in the United States tend to be considered a new model minority because of the perception that they perform academically better than their African American peers. Yet, Black immigrant youth face challenges with literacy performance that often go unnoticed by teachers, which amplifies the invisibility of their literacies. I assert that nuances presented in the literacies of Black immigrant youth as they become Black, become immigrants, and become speakers of racialized Englishes, necessitate the use of a theoretical lens that allows researchers to foreground race and mediate the linguistic and cultural expectations of these youth. To demonstrate, I propose the lens of translanguaging premised on an integrated model of multilingualism. This perspective provides a basis for foregrounding racialized language to facilitate an ideological understanding surrounding how Black immigrant youth leverage Englishes in their individual linguistic repertoires (i.e., I-languages) to enact literacies. At the same time, it provides an opportunity to understand how these youth engage the often-imposed structural rules of shared grammars within and across these Englishes (i.e., E-languages) in ways that influence these literacies. By presenting Black Caribbean immigrant youth's literacies as a unique example to foreground racialized language via translanguaging for examining the Englishes of bidialectal youth, I encourage researchers to empower youth to navigate theoretical tensions that remain central to translanguaging research. More broadly, I invite researchers to think beyond dichotomies while clarifying what it means for youth of color from varied backgrounds to leverage their literacies and thrive.